Adherence Assessment on Hypertension Therapy Using The Pill Count Method In Lubuk Kilangan Health Center, Indonesia - Fitria, Najmiatul; Lailaturrahmi, Lailaturrahmi; Sari, Yelly Oktavia; Anata, Fahira Tri; Husnia, Khairatul (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
Adherence is a major problem in hypertension treatment. Patients' adherence can be evaluated through pill count by counting the remaining amount of the patient's medication at the beginning and the end, using a pillbox as a tool to improve patient medication adherence. The purpose of this study was to describe the differences in adherence between patients who used the pillbox and without the pillbox. The research method used is Pretest-Posttest Control Group Design. The sample of this study is Prolanis (Chronic Disease Management Program) patients in 2021 at the Lubuk Kilangan Health Center in Padang City. They meet the inclusion and exclusion criteria that have been set. Sampling was carried out by total sample and obtained 70 subjects divided into the treatment group and the control group. The research technique used a Home Medication Review (HMR). The results of the study using the Mann-Whitney Test statistical test on adherence (p = 0.007) showed a value (p<0.05). It can be concluded that there are differences in adherence before and after the intervention. This result indicates that adherence is higher in patients who use the pillbox than those without the pillbox.